2022
DOI: 10.1007/s00210-022-02284-6
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline and COVID-19: vis-à-vis conjectured

Abstract: Coronavirus disease 2019 (COVID-19) is a current pandemic disease caused by a novel severe acute respiratory syndrome coronavirus virus respiratory type 2 (SARS-CoV-2). SARS-CoV-2 infection is linked with various neurological manifestations due to cytokine-induced disruption of the blood brain barrier (BBB), neuroinflammation, and peripheral neuronal injury, or due to direct SARS-CoV-2 neurotropism. Of note, many repurposed agents were included in different therapeutic protocols in the management of COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 117 publications
0
38
0
5
Order By: Relevance
“… 47 , 48 It has been shown that augmentation of AngII in SARS‐CoV‐2 infection can activate several inflammatory signaling pathways like NF‐κB, NLRP3 inflammasome and a disintegrin and metalloprotease 17 (ADAM17) with subsequent release of proinflammatory cytokines. 49 , 50 SARS‐CoV‐2 can directly activate NF‐κB and NLRP3 inflammasome with the succeeding release of proinflammatory cytokines like IL‐6 and TNF‐α. 51 , 52 Furthermore, the binding of IL‐6 to its IL‐6 receptor trigger other inflammatory signaling pathways like signal transducer and activator of transcription 3 (STAT3) which is involved in the release of proinflammatory cytokines.…”
Section: Cs In Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“… 47 , 48 It has been shown that augmentation of AngII in SARS‐CoV‐2 infection can activate several inflammatory signaling pathways like NF‐κB, NLRP3 inflammasome and a disintegrin and metalloprotease 17 (ADAM17) with subsequent release of proinflammatory cytokines. 49 , 50 SARS‐CoV‐2 can directly activate NF‐κB and NLRP3 inflammasome with the succeeding release of proinflammatory cytokines like IL‐6 and TNF‐α. 51 , 52 Furthermore, the binding of IL‐6 to its IL‐6 receptor trigger other inflammatory signaling pathways like signal transducer and activator of transcription 3 (STAT3) which is involved in the release of proinflammatory cytokines.…”
Section: Cs In Covid‐19mentioning
confidence: 99%
“…In Covid‐19, oxidative stress is developed due to the overproduction of ROS and reduction of endogenous antioxidant capacity. 15 , 49 The risk factors for the development of oxidative stress in Covid‐19 are old age, male sex, black race, obesity, and diabetes mellitus. 30 , 122 , 123 Exaggerated oxidative stress leads to the propagation of oxidative storm which increases Covid‐19 severity.…”
Section: Oxidative Storm In Covid‐19mentioning
confidence: 99%
“…Furthermore, S1P is involved in SARS-CoV-2 pathogenesis and infection through transmembrane protease serine 2 (TMPRSS2)/ACE2 axis induction. In addition, activation of protective ACE2 is associated with the expression of S1P and S1PR [ 63 , 68 ] (Fig. 2 ).…”
Section: Role Of S1p Pathway In Covid-19mentioning
confidence: 99%
“…Autophagy, which is necessary for viral clearance, is severely impaired in SARS‐CoV‐2 infection, 101,102 so activation of autophagy may enhance COVID‐19 recovery. A previous study illustrated that DTN promotes activity of autophagy 103 .…”
Section: Role Of Ryanodine Receptors and Dantrolene In Covid‐19mentioning
confidence: 99%